2018
DOI: 10.1111/1365-2656.12817
|View full text |Cite
|
Sign up to set email alerts
|

Linking demographic processes and foraging ecology in wandering albatross—Conservation implications

Abstract: Population dynamics and foraging ecology are two fields of the population ecology that are generally studied separately. Yet, foraging determines allocation processes and therefore demography. Studies on wandering albatrosses Diomedea exulans over the past 50 years have contributed to better understand the links between population dynamics and foraging ecology. This article reviews how these two facets of population ecology have been combined to better understand ecological processes, but also have contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…Indeed, juveniles of several species of albatrosses and petrels disperse more widely and more to the north of the species range, often to less productive waters than adults (Riotte‐Lambert & Weimerskirch, ; Weimerskirch et al, ). Similarly, the often substantial individual variability among juvenile and immature birds can be difficult to capture with limited tracking effort (Clay, ), but as immatures age, their distributions become increasingly similar to those of adults (de Grissac, Börger, Guitteaud, & Weimerskirch, ; Weimerskirch, ). Accounting for all life‐history stages in distribution maps may be even more relevant for near‐obligate biennial breeders such as the great Diomedea spp., sooty Phoebetria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, juveniles of several species of albatrosses and petrels disperse more widely and more to the north of the species range, often to less productive waters than adults (Riotte‐Lambert & Weimerskirch, ; Weimerskirch et al, ). Similarly, the often substantial individual variability among juvenile and immature birds can be difficult to capture with limited tracking effort (Clay, ), but as immatures age, their distributions become increasingly similar to those of adults (de Grissac, Börger, Guitteaud, & Weimerskirch, ; Weimerskirch, ). Accounting for all life‐history stages in distribution maps may be even more relevant for near‐obligate biennial breeders such as the great Diomedea spp., sooty Phoebetria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates increase dramatically between fledglings and 1‐yr‐olds in Magellanic Penguins (this study). In Wandering Albatross, the foraging skills of fledglings improve rapidly over the first few months at sea, after which they are comparable to those of adults (Weimerskirch ). We found that survival decreased again for individuals ≥19 yr of age, potentially because of senescence‐related reductions in foraging efficiency (e.g., Zimmer et al.…”
Section: Discussionmentioning
confidence: 99%
“…The PCoD approach provides a means for investigating the physiological and the behavioral drivers of an individual's response to human disturbance, and therefore a population's viability (Cooke et al, 2014). Linking behavioral and physiological changes to demography also facilitates prediction of the effects of climate change on wildlife populations (e.g., Desprez, Jenouvrier, Barbraud, Delord, & Weimerskirch, 2018;Pagano et al, 2018;Weimerskirch, 2018). More generally, the nonlethal effects of human disturbance and environmental change and their repercussions at a population level can be viewed as examples of the fundamental processes regulating trait-mediated, indirect ecological interactions (Ripple & Beschta, 2012;Werner & Peacor, 2003).…”
Section: Appli C Ati On S Of P Cod Model Smentioning
confidence: 99%